Disentangling Interacting Symmetry-Protected Phases of Fermions in Two Dimensions - Tyler D. Ellison (American Physical Society, 2019)
We construct fixed point lattice models for group supercohomology symmetry-protected topological phases of fermions (2+1)D. A key feature of our approach is to construct finite depth circuits of local unitaries that explicitly build the ground states from a tensor product state. We then recover the classification of fermionic symmetry-protected topological phases, including the group structure under stacking, from the algebraic composition rules of these circuits. Furthermore, we show that the circuits are symmetric, implying that the group supercohomology phases can be many-body localized. Our strategy involves first building an auxiliary bosonic model, and then fermionizing it using the duality of Chen, Kapustin, and Radicevic. One benefit of this approach is that it clearly disentangles the role of the algebraic group supercohomology data, which are used to build the auxiliary bosonic model, from that of the spin structure, which is combinatorially encoded in the lattice and enters only in the fermionization step. In particular this allows us to study our models on 2D spatial manifolds of any topology, and to define a lattice-level procedure for ungauging fermion parity.